ANALYISIS OF SENIOR CLASSROOM STUDENTS ENGLISH LEARNING CHALLENGES WITHIN CERTAIN PRIVATE SECONDARY SCHOOLS IN GOMA - Balume Kamaro Gentil; Nom Et Post Noms (IJRDO- Journal of Educational Research, 2024)
This work targeted to analyze English learning challenges faced by senior class learners within some private secondary schools in Goma and which have impacted inadequately their learning outcomes in this language. Evidently, this study contributes to enabling the envisaged classes’ EFL teachers to find out useful key guidelines which they ought to apply via their teaching in order to facilitate the targeted students to face an efficient learning of English. Qualitative and quantitative methods were resorted to for the collection of valid and reliable data from a sample of 100 students enrolled in senior classrooms (3rd and 4th forms) within the targeted schools. The results demonstrated that more teachers worked as principal actors who have led some of their students to view English with negative appreciation and which affected their learning performance in SLL skills inconsistently. Evidently, these learners felt that though English is a most worldwide used language, it is however, a most complicated language which cannot be comprehended neither grasped perfectly. Henceforth, I have provided useful suggestions that should help their teachers to renovate their teaching effectively in order to push them to learn English more successfully.